An Experimental Study for Enhancing the Performance of the Photovoltaic Module Using Forced Air - Malik F. Jaffar; Abdulrahman Th. Mohammad; Ahmed Qasim Ahmed (Journal of Techniques)
The performance of the photovoltaic (PV) module is greatly affected by ambient conditions such as solar irradiance and air temperature.  Increasing the ambient temperature plays a major role in raising the PV temperature and then reducing its performance by reducing its voltage. In this work, an experimental investigation was carried out to enhance the performance of the PV module by using the thermal-photovoltaic (PVT) technique. The PVT was prepared by integrating the PV module with an air duct. The air was forced by an electrical centrifugal fan with variable speeds (1.5, 2.5, and 3.5 m/s). The analysis of the obtained results showed that the PVT technique can lower the PV temperature from 5 to 16 °C when the air volume flow rate changes from 335 to 760 m3/h.  In contrast, the maximum enhancement of PVT power was recorded at 8.2% at a maximum air volume flow rate of 760 m3/h causing a maximum electrical efficiency of about 17.9%.